Recent progress in organic sensitizers for dye-sensitized solar cells - Lee, Chuan-Pei; Lin, Ryan Yeh-Yung; Lin, Lu-Yin; Li, Chun-Ting; Chu, Te-Chun; Sun, Shih-Sheng; Lin, Jiann T; Ho, Kuo-Chuan (RSC advances, 2015)
Dye-sensitized solar cells (DSSCs) are fabricated using low-cost materials and a simple fabrication process; these advantages make them attractive candidates for research on next generation solar cells. In this type of solar cell, dye-sensitized metal oxide electrodes play an important role for achieving high performance since the porous metal oxide films provide large specific surface area for dye loading and the dye molecule possesses broad absorption covering the visible region or even part of the near-infrared (NIR). Recently, metal-free sensitizers have made great progress and become the most potential alternatives. This review mainly focuses on recent progress in metal-free sensitizers for applications in DSSCs. Besides, we also briefly report DSSCs with near-infrared (NIR) organic sensitizers, which provide the possibility to extend the absorption threshold of the sensitizers in the NIR region. Finally, special consideration has been paid to panchromatic engineering, co-sensitization, a key technique to achieve whole light absorption for improving the performance of DSSCs. This review focuses on recent progress of metal-free sensitizers and on panchromatic engineering of co-sensitization in dye-sensitized solar cells (DSSCs).